2017
DOI: 10.14814/phy2.13449
|View full text |Cite
|
Sign up to set email alerts
|

Complex restitution behavior and reentry in a cardiac tissue model for neonatal mice

Abstract: Spatiotemporal dynamics in cardiac tissue emerging from the coupling of individual cardiomyocytes underlie the heart's normal rhythm as well as undesired and possibly life‐threatening arrhythmias. While single cells and their transmembrane currents have been studied extensively, systematically investigating spatiotemporal dynamics is complicated by the nontrivial relationship between single‐cell and emergent tissue properties. Mathematical models have been employed to bridge this gap and contribute to a deepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…A study of the restitution characteristics for this system, as presented in Ref. (39) (see Figures 5 A and B, therein), indicated that wave breaks occurred in a stable parameter régime, thus proving the robustness and restitutionindependence of our proposed mechanism for wave breaks.…”
Section: R a F Tsupporting
confidence: 61%
“…A study of the restitution characteristics for this system, as presented in Ref. (39) (see Figures 5 A and B, therein), indicated that wave breaks occurred in a stable parameter régime, thus proving the robustness and restitutionindependence of our proposed mechanism for wave breaks.…”
Section: R a F Tsupporting
confidence: 61%
“…APs in small tissue preparations are slightly different from those in single cardiomyocytes. Differences can arise from electrotonic coupling and the mixture of cells including fibroblasts that are able to modify the EP ( Kohl and Gourdie, 2014 ; Mayer et al, 2017 ; Hall et al, 2021 ). This can hamper the fitting of the APs and consequently, the estimation of the maximum conductances and pharmacological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, this is a primary culture of animal cells, that is, a cell culture obtained by isolating cells of a certain type of tissue directly from an organ of a living organism (ex vivo) [95,96]. Cardiomyocytes cannot combine into excitable tissue after a certain period of their development.…”
Section: Application Of Different Cell Types To Simulate Cardiac Tiss...mentioning
confidence: 99%